Therapeutic Plasma Concentrations of Antidepressants and Antipsychotics: Lessons from PET Imaging - Gründer, G.; Hiemke, C.; Paulzen, M.; Veselinovic, T.; Vernaleken, I. (Pharmacopsychiatry, 2011)
Therapeutic Drug Monitoring (TDM) of psychotropic drugs is strongly depending on the validity of recommended therapeutic plasma concentration reference ranges. Rational pharmacotherapy is based on the assumption that plasma concentrations are directly related to target occupancy by the respective drug. Here we show that positron emission tomography (PET) of molecular drug targets in the brain (neuroreceptors and transporters) allows for establishment of these relationships, thereby providing guidance for TDM services. Associations between brain target occupancy, plasma concentrations, and clinical effects and adverse reactions will be discussed for the most commonly used antidepressant and antipsychotic drugs.
Keywords: therapeutic drug monitoring (TDM); positron emission tomography (PET); plasma concentration; antidepressant; antipsychotic